(untitled) (The Agriculturists, 2016)
A survey was conducted to assess the export supply and value chain analyses of okra (Abelmoschus esculentus L.) in Bangladesh. The survey was consisted of primary and secondary data from semi-structured interview of key persons involved in the supply chains of export market of okra and from the review of relevant reports and literature. Primary data were collected from 40 middlemen (from Ulokhola-10, Kawranbazar-7, Shambazar-8, Jatrabaribazar-5, Chandina-10), 5 service providers and 20 okra exporters of Dhaka city. It was found that the supply chain was fragmented and complex. The middlemen predominantly controlled the supply chains. Post-harvest management was poor, resulting low quality of the produce and low prices in the export market. The supply chain indicated that, the growers consumed 7.8% of their own product while 92.2% was sold out. About 28% farmers sold their okra at the field/farm-gates and 72% was sold in the local markets. The value chain analyses (VCA) revealed that, the net profit margin was 15.77 Tk/kg for both the UK and the Middle East markets whereas the net profit was 5.86 Tk/kg in local markets. The cost of airfreight was highest (63.97%) of all costs followed by the production cost of okra (16.85%) and the cost of packing (13.40%). The Agriculturists 2015; 13(1) 133-139